Commentary: Do plants perceive sound? A mechanistic perspective on sound-induced plant responses - Ramasubramanian Sabarivasan; R. Jeevanraj; Kandasamy Adhisankaran; P. Manjunath (Plant Science, 2026)

Investigative study on hardness and yield strength of Al6061/Sic/Gr. hybrid composite and prediction using machine learning technique - Bharath L; Manjunath T V; Arun Kumar K; Chethan Kumar R; Kiran Kumar S; Prajwal M; Vikas L Lamani (Next Research, 2025)

Exploring the Potential of miRNA-92a-3p as Lead for Sequence-Based Therapies for Malaria - Sowmya R. Prabhu; Sayandrila Paul; Shashikiran Umakanth; Manjunath Hande; Abdul Vahab Saadi; Himanshu Gupta; Kapaettu Satyamoorthy (Acta Parasitologica, 2025)

Engineering ZnO-TiO2 composite gas sensors for improved air pollutant detection through annealing temperature optimization - B. Renganathan; Manjunath S. Kamath; Ganesh M. Ramanujam; R. Vasanthapriya; A.R. Ganesan; Subha Krishna Rao (Journal of Water Process Engineering, 2025)

Butterfly Communities of Bangalore University Campus, Bengaluru, India: Host/Nectar Plant Interactions and Environmental Influences - S. Rajashekara; L. K. Eregowda; G. S. Manjunath; T. K. Manoranjini; R. D. Prathibha; M. G. Venkatesha (Proceedings of the Zoological Society, 2025)

Performance evaluation of coffee husk ash based one-part self compacting alkali activated slag concrete mixes - R. Manjunath; J. R. Pushya; K. A. Abhilash Kumar; Kiran K. Shetty (Innovative Infrastructure Solutions, 2025)
Alkali-activated binders are low-carbon alternatives to cement, produced by reacting an alkali activator with an alumino-silicate precursor. However, common alkaline activators like NaOH and Na 2 SiO 3 are highly corrosive, limiting their practical use. This study developed one-part alkali-activated binders from agricultural and industrial waste to address challenges posed by conventional two-part systems. Further performance evaluation of alkali activated slag mixes were evaluated using the developed solid activator. The approach supports sustainable waste management, offers an eco-friendly alternative to Portland cement, and lowers carbon emissions. Using solid alkali-activator sodium metasilicate and precursors like coffee husk ash (CHA), Ground granulated blast furnace slag, and ferrochrome slag, one-part alkali-activated self-compacting concrete (OPASC) mixes were created through Taguchi design experiments. The experimental trials of OPASC were evaluated for fresh, mechanical, microstructural, and durability properties. Results showed flowability between 700 and 765 mm, compressive strength of 50–63 MPa, flexural strength of 3.05–3.58 MPa, splitting tensile strength of 2.7–3.58 MPa, and elastic moduli of 30–32 GPa. These properties were comparable to the reference ordinary Portland cement self-compacting concrete mix, which had a compressive strength of 55 MPa, flexural strength of 4 MPa, splitting tensile strength of 2.8 MPa, and elastic modulus of 30 GPa at 28 days. The OPASC mix showed lower water absorption, high concrete quality (UPV > 4.5), and better performance at elevated temperatures. The study suggests that CHA-based alkali-activated materials can be effectively used, reducing waste and offering viable structural properties.

Molecular delineation and genetic diversity of Fusarium species complex causing tea dieback in India and their sensitivity to fungicides - Abhay K. Pandey; Manjunath Hubballi; Harshit K. Sharma; R. Ramesh; Somnath Roy; K. Dinesh; Azariah Babu (Crop Protection, 2024)

Characterization of Puccinia horiana causing Chrysanthemum rust disease and its management by altering planting date and foliar application of fungicide - R Munilakshmi; Anjaneya Reddy B; Manjunath Hubballi; Rajiv Kumar; B Mahesha; Jayashree Ugalat (Indian Phytopathology, 2023)

Erythrocyte miRNA-92a-3p interactions with PfEMP1 as determinants of clinical malaria - Sowmya R. Prabhu; Akshay Pramod Ware; Shashikiran Umakanth; Manjunath Hande; Chakrapani Mahabala; Abdul Vahab Saadi; Kapaettu Satyamoorthy (Functional & Integrative Genomics, 2023)
Based on the recently added high throughput analysis data on small noncoding RNAs in modulating disease pathophysiology of malaria, we performed an integrative computational analysis for exploring the role of human-host erythrocytic microRNAs (miRNAs) and their influence on parasite survival and host homeostasis. An in silico analysis was performed on transcriptomic datasets accessed from PlasmoDB and Gene Expression Omnibus (GEO) repositories analyzed using miRanda, miRTarBase, mirDIP, and miRDB to identify the candidate miRNAs that were further subjected to network analysis using MCODE and DAVID. This was followed by immune infiltration analysis and screening for RNA degradation mechanisms. Seven erythrocytic miRNAs, miR-451a, miR-92a-3p, miR-16-5p, miR-142-3p, miR-15b-5p, miR-19b-3p, and miR-223-3p showed favourable interactions with parasite genes expressed during blood stage infection. The miR-92a-3p that targeted the virulence gene PfEMP1 showed drastic reduction during infection. Performing pathway analysis for the human-host gene targets for the miRNA identified TOB1 , TOB2 , CNOT4 , and XRN1 genes that are associated to RNA degradation processes, with the exoribonuclease XRN1 , highly enriched in the malarial samples. On evaluating the role of exoribonucleases in miRNA degradation further, the pattern of Plasmodium falciparum _XRN1 showed increased levels during infection thus suggesting a defensive role for parasite survival. This study identifies miR-92a-3p, a member of C13orf25/ miR-17-92 cluster, as a novel miRNA inhibitor of the crucial parasite genes responsible for symptomatic malaria. Evidence for a plausible link to chromosome 13q31.3 loci controlling the epigenetic disease regulation is also suggested.

The Role of a Gut Microbial-Derived Metabolite, Trimethylamine N-Oxide (TMAO), in Neurological Disorders - Sankar Simla Praveenraj; Sharma Sonali; Nikhilesh Anand; Hediyal Ahmed Tousif; Chandrasekaran Vichitra; Manjunath Kalyan; Perumalswamy Velumani Kanna; Kumar A. Chandana; Paneyala Shasthara; Arehally M. Mahalakshmi; Jian Yang; Seithikurippu R. Pandi-Perumal; et al. (Molecular Neurobiology, 2022)

Geochemical constraints of bulk rocks and in-situ zircon from the granitoids of the Hungund Schist Belt: An insight for hydrothermal activity - Shivani Hulaji; V S Hegde; Xian-Hua Li; Li Su; Asim R Pratihari; Manjunath Paltekar (Journal of Earth System Science, 2022)

Impact of Sleep Deprivation on Major Neuroinflammatory Signal Transduction Pathways - Arehally M. Mahalakshmi; Prithvi Lokesh; Tousif Ahmed Hediyal; Manjunath Kalyan; Chandrasekaran Vichitra; Musthafa Mohamed Essa; M. Walid Qoronfleh; Seithikurippu R. Pandi-Perumal; Saravana Babu Chidambaram (Sleep and Vigilance, 2022)

Comparative performance of semi-empirical based remote sensing and crop simulation model for cotton yield prediction - N. R. Prasad; N. R. Patel; Abhishek Danodia; K. R. Manjunath (Modeling Earth Systems and Environment, 2022)

Effects of fiber addition on performance of high-performance alkali activated slag concrete mixes: An experimental evaluation - R. Manjunath; Mattur C. Narasimhan; Shivam Kumar (European Journal of Environmental and Civil Engineering, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Geochemistry of heavy minerals from Uttara Kannada beach sediments, West Coast of India: an insight into provenance studies - Manjunath Paltekar; V. S. Hegde; Shivani Hulaji; Asim R. Pratihari; M. M. Korkoppa (Journal of Sedimentary Environments, 2021)

Mechanistic Deconvolution of Oral Absorption Model with Dynamic Gastrointestinal Fluid to Predict Regional Rate and Extent of GI Drug Dissolution - Alex Yu; Mark J. Koenigsknecht; Bart Hens; Jason R. Baker; Bo Wen; Trachette L. Jackson; Manjunath P. Pai; William Hasler; Gordon L. Amidon; Duxin Sun (The AAPS Journal, 2020)

Quantitative Analysis of Phyllanthus Species for Bioactive Molecules Using High-Pressure Liquid Chromatography and Liquid Chromatography–Mass Spectrometry - A. Muthusamy; E. R. Sanjay; H. N. Nagendra Prasad; M. Radhakrishna Rao; B. Manjunath Joshi; S. Padmalatha Rai; K. Satyamoorthy (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Genotype phenotype correlation in Asian Indian von Hippel–Lindau (VHL) syndrome patients with pheochromocytoma/paraganglioma - Nilesh Lomte; Sanjeet Kumar; Vijaya Sarathi; Reshma Pandit; Manjunath Goroshi; Swati Jadhav; Anurag R. Lila; Tushar Bandgar; Nalini S. Shah (Familial Cancer, 2018)

Carbon Footprint of Crop Cultivation Process Under Semiarid Conditions - A. S. Devakumar; R. Pardis; V. Manjunath (Agricultural Research, 2018)

Microbial and Enzyme Activities and Carbon Stock in Unique Coastal Acid Saline Soils of Goa - G. R. Mahajan; B. L. Manjunath; A. M. Latare; Ruenna D’Souza; Shashi Vishwakarma; N. P. Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Multiple endocrine neoplasia type 1 syndrome: single centre experience from western India - Manjunath Goroshi; Tushar Bandgar; Anurag R. Lila; Swati Sachin Jadhav; Shruti Khare; Shailesh V. Shrikhande; Shinya Uchino; Abhay N. Dalvi; Nalini S. Shah (Familial Cancer, 2016)

Monsoon paddy monitoring and assessment using synthetic aperture radar data under BGREI programme in Odisha, India - Dipanwita Haldar; K. R. Manjunath; Sushma Panigrahy; Varunika Jain; R. S. Gopalan; Mukesh Khullar; Manab Chakraborty; J. S. Parihar (Paddy and Water Environment, 2015)

Developing Spectral Library of Major Plant Species of Western Himalayas Using Ground Observations - K. R. Manjunath; Amit Kumar; Mehra Meenakshi; R. Renu; S. K. Uniyal; R. D. Singh; P. S. Ahuja; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2014)

Resistance reaction of gene introgressed lines against rice blast (Pyricularia oryzae) disease - B. Divya; S. Robin; R. Rabindran; H. Manjunath; P. Valarmathi; A. John Joel (Australasian Plant Pathology, 2014)

Deducing Rice Crop Dynamics and Cultural Types of Bangladesh Using Geospatial Techniques - Revati More; K. R. Manjunath (Journal of the Indian Society of Remote Sensing, 2013)

Synthesis of some novel 1,2,4-triazole and 1,3,4-oxadiazole derivatives of biological interest - Bhimagouda S. Patil; G. Krishnamurthy; M. R. Lokesh; N. D. Shashikumar; H. S. Bhojya Naik; Prashant R. Latthe; Manjunath Ghate (Medicinal Chemistry Research, 2013)

Greenhouse gas emissions from Indian livestock - Abha Chhabra; K. R. Manjunath; Sushma Panigrahy; J. S. Parihar (Climatic Change, 2013)

Molecular epidemiology and characterisation of MRSA isolates from Trinidad and Tobago - S. Monecke; H. Nitschke; P. Slickers; R. Ehricht; W. Swanston; M. Manjunath; R. Roberts; P. E. Akpaka (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Photosynthetic rate model in response to environmental parameters for Avicennia marina (Forssk.) Veih. in an Indian mangrove forest - Tanumi Kumar; Sushma Panigrahy; K. R. Manjunath; Chandra Prakash Singh (Acta Physiologiae Plantarum, 2012)

Hyperspectral leaf signature as an added dimension for species discrimination: case study of four tropical mangroves - Sushma Panigrahy; Tanumi Kumar; K. R. Manjunath (Wetlands Ecology and Management, 2012)

Discrimination of Spectrally-Close Crops Using Ground-Based Hyperspectral Data - K. R. Manjunath; Shibendu Shankar Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2011)

Methane Emission Pattern of Indian Rice-Ecosystems - K. R. Manjunath; Sushma Panigrahy; T. K. Adhya; V. Beri; K. V. Rao; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2011)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

Stone Columns with Vertical Circumferential Nails: Laboratory Model Study - R. Shivashankar; M. R. Dheerendra Babu; Sitaram Nayak; R. Manjunath (Geotechnical and Geological Engineering, 2010)

Induction of MHC-I and thymic depletion due to replication of JEV in mouse brain - Y. Kavitha; R. Manjunath (Archives of Virology, 2004)

Wheat growth profile: satellite monitoring and crop yield modelling - K. R. Manjunath; M. B. Potdar (Journal of the Indian Society of Remote Sensing, 2004)

Hyperhomocysteinemia: An emerging risk factor for cardiovascular disease - V. Govindaraju; Neelam; C. N. Manjunath; H. Venkataramiah; T. R. Raghu (Indian Journal of Clinical Biochemistry, 2003)

Evaluation of RADARSAT ScanSAR synthetic aperture radar data for rice crop inventory and monitoring - S. Panigrahy; M. Chakraborty; K. R. Manjunath; N. Kundu; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2000)

Development and validation of spectrometeorological yield models of mustard oil seed crop in Rajasthan state - M. B. Potdar; K. R. Manjunath; N. L. Purohit (Journal of the Indian Society of Remote Sensing, 1999)

Evaluation of spectral bands and spatial resolution of LISS II and LISS III sensors on-board IRS satellites for crop identification - K R Manjunath; N Kundu; S Panigrahy (Journal of the Indian Society of Remote Sensing, 1998)

In vivo clearance of Japanese encephalitis virus by adoptively transferred virus specific cytotoxic T lymphocytes - A. Desai; K. Murali-Krishna; B. Ramireddy; V. Ravi; R. Manjunath (Journal of Biosciences, 1997)

Japanese encephalitis virus infection of mouse cell lines: ability to prime mice for generation of virus specific cytotoxic T lymphocytes and differences in CTL recognisable viral determinants - K. Murali-Krishna; V. Ravi; R. Manjunath (Archives of Virology, 1995)

Correlation of histologic types of carcinoma of the uterine cervix and human papillomavirus and herpes simplex virus type 2 DNA sequences in the uterine cervical biopsies - P. Seth; H. Kaur; R. Kaur; K. Verma; N. Manjunath (Archives of Virology, 1988)